2017
DOI: 10.1016/s2214-109x(16)30242-x
|View full text |Cite|
|
Sign up to set email alerts
|

Mass deworming to improve developmental health and wellbeing of children in low-income and middle-income countries: a systematic review and network meta-analysis

Abstract: Canadian Institutes of Health Research and WHO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 24 publications
7
77
1
Order By: Relevance
“…This is not true since reviews drawing on programme theory that collect evidence on outcomes along the causal chain can explain heterogeneity in findings -usually variation in quality of life outcomes due to differences in rates of programme adherence (for example, Welch et al 2017). However, analysis of the rest of the causal chain usually requires turning to evidence in studies which are often excluded from systematic reviews on the grounds of study design.…”
Section: Fostering Learning By Using Programme Theory and Telling A Gmentioning
confidence: 99%
“…This is not true since reviews drawing on programme theory that collect evidence on outcomes along the causal chain can explain heterogeneity in findings -usually variation in quality of life outcomes due to differences in rates of programme adherence (for example, Welch et al 2017). However, analysis of the rest of the causal chain usually requires turning to evidence in studies which are often excluded from systematic reviews on the grounds of study design.…”
Section: Fostering Learning By Using Programme Theory and Telling A Gmentioning
confidence: 99%
“…The National Deworming Day programme was initiated by the Indian government in February 2015 with the aim of deworming every child between 1 and 19 yr of age biannually and is one of the largest national public health programmes in the world31. While there has been considerable debate regarding the effectiveness of mass deworming programmes in the academic community323334, several studies conducted in India have suggested benefit.…”
Section: Recommended Control Strategiesmentioning
confidence: 99%
“…In this study, where undernourished pre-SAC (PSAC) were randomized to receive either tetramisole every four months or placebo, the prevalence of Ascaris decreased in the treatment group (although it was not eliminated) and the nutritional status of the children receiving treatment improved significantly at 8-12 months. In addition, there are several observational studies that have shown improvements in multiple outcomes including weight and haemoglobin levels in children in communities following deworming143234. However, treatment of infected individuals and subsequent resolution of infection do not prevent recurrence of infection.…”
Section: Recommended Control Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a systematic review found the evidence insufficient to link helminths to cognitive performance 16 and a further meta-analysis concluded that mass deworming of children had little or no effect on weight, height, cognition, school attendance or mortality. 17 …”
Section: How Much Do We Benefit From Mda?mentioning
confidence: 99%